Review: Clinical, neuropathological and genetic features of Lewy body dementias. (20th May 2019) - Hansen, D.; Ling, H.; Lashley, T.; Holton, J. L.; Warner, T. T.
Abstract : Lewy body dementias are the second most common neurodegenerative dementias after Alzheimer's disease and include dementia with Lewy bodies and Parkinson's disease dementia. They share similar clinical and neuropathological features but differ in the time of dementia and parkinsonism onset. Although Lewy bodies are their main pathological hallmark, several studies have shown the emerging importance of Alzheimer's disease pathology. Clinical amyloid‐β imaging using Pittsburgh Compound B (PiB) supports neuropathological studies which found that amyloid‐β pathology is more common in dementia with Lewy bodies than in Parkinson's disease dementia. Nevertheless, other co‐occurring pathologies, such as cerebral amyloid angiopathy, TDP‐43 pathology and synaptic pathology may also influence the development of neurodegeneration and dementia. Recent genetic studies demonstrated an important role of APOE genotype and other genes such as GBA and SNCA which seem to be involved in the pathophysiology of Lewy body dementias. The aim of this article is to review the main clinical, neuropathological and genetic aspects of dementia with Lewy bodies and Parkinson's disease dementia. This is particularly relevant as future management for these two conditions may differ.